The Influence of Family Support, Perceived Digital Competence And Attitude, and Learning Agility on The Speed of Completing Student Studies with The Role of Academic Self-Efficacy as A Mediation Variable - I Nyoman Wijana (STKIP Singkawang, 2022)
This study aims to determine whether there is a relationship between Family Support, Perceived Digital Competence and Attitude, Learning Agility, and Academic Self-Efficacy in the Speed of Completing Studies. In addition to knowing the effect of Perceived Digital Competence and Attitude and Learning Agility on Academic Self-Efficacy. This research was conducted on Undergraduate and Master program students at the Gde Pudja Mataram State Hindu Institute (IAHN). The data collection technique in this study was random sampling to obtain 100 students in the Bachelor's program and Master's program at IAHN Gde Pudja Mataram. The data analysis technique in this study uses a Structural Equation Model (SEM) approach with the help of the Smart PLS application. The results of this study indicate that: 1) family support has a significant positive effect on the speed of completing studies, 2) perceived digital competence and attitude do not affect the speed of completing studies, 3) Learning Agility does not affect the speed of completing studies, 4) family support has a significant positive effect on academic self-efficacy, 5) perceived digital competence and attitude do not affect academic self-efficacy, 6) Learning Agility does not affect academic self-efficacy, and 7) academic self-efficacy has a significant positive effect on the speed of completing studies. So it can be concluded that what can affect the speed of completing studies for Undergraduate and Master program students at IAHN Gde Pudja Mataram are internal factors, namely from oneself (academic self-efficacy), and external factors, namely support from family.